2007
DOI: 10.1152/ajpcell.00274.2006
|View full text |Cite
|
Sign up to set email alerts
|

SCAM analysis reveals a discrete region of the pore turret that modulates slow inactivation in Kv1.5

Abstract: In Kv1.5, protonation of histidine 463 in the S5-P linker (turret) increases the rate of depolarization-induced inactivation and decreases the peak current amplitude. In this study, we examined how amino acid substitutions that altered the physico-chemical properties of the side chain at position 463 affected slow inactivation and then used the substituted cysteine accessibility method (SCAM) to probe the turret region (E456-P468) to determine whether residue 463 was unique in its ability to modulate the macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…However, a previous study showed that the alanine substitution of His463 (H463A) in hKv1.5 channel results in a marked acceleration of current inactivation (Eduljee et al, 2007). We therefore substituted His463 to cysteine (H463C), which has been demonstrated to exhibit an inactivation rate qualitatively similar to that of the wild type hKv1.5 (Eduljee et al, 2007). It should also be noted that Thr480, Ile508 and Val516 are predicted to face toward the central cavity (Decher et al, 2006;Eldstrom et al, 2007;Tamargo et al, 2009).…”
Section: Putative Target Amino Acids Involved In Propofol-induced Blomentioning
confidence: 98%
See 1 more Smart Citation
“…However, a previous study showed that the alanine substitution of His463 (H463A) in hKv1.5 channel results in a marked acceleration of current inactivation (Eduljee et al, 2007). We therefore substituted His463 to cysteine (H463C), which has been demonstrated to exhibit an inactivation rate qualitatively similar to that of the wild type hKv1.5 (Eduljee et al, 2007). It should also be noted that Thr480, Ile508 and Val516 are predicted to face toward the central cavity (Decher et al, 2006;Eldstrom et al, 2007;Tamargo et al, 2009).…”
Section: Putative Target Amino Acids Involved In Propofol-induced Blomentioning
confidence: 98%
“…Wherever possible, alanine was chosen for the substitution of wild type amino acids because it is expected to have small effects on the protein secondary structure (Eldstrom et al, 2007;Hockerman et al, 1995;Mitcheson et al, 2000). However, a previous study showed that the alanine substitution of His463 (H463A) in hKv1.5 channel results in a marked acceleration of current inactivation (Eduljee et al, 2007). We therefore substituted His463 to cysteine (H463C), which has been demonstrated to exhibit an inactivation rate qualitatively similar to that of the wild type hKv1.5 (Eduljee et al, 2007).…”
Section: Putative Target Amino Acids Involved In Propofol-induced Blomentioning
confidence: 99%
“…Other mutations in Shaker channels that modulate slow inactivation include E418 and V463 ( Hoshi et al, 1991 ;Larsson and Elinder, 2000 ), but unfortunately we were unable to obtain current expression or fl uorescence recordings in oocytes from the equivalent residues E456Q or E456C in Kv1.5 (see also Eduljee et al, 2007 ), or the equivalent residues to V463 in Shaker . However, another residue that modulates P/C-type inactivation in Kv1.5 is the His in the pore turret ( Kehl et al, 2002 ).…”
Section: The Dequenching Component Of Fluorescence Is Associated Withmentioning
confidence: 99%
“…9), in which the nonconservative mutants, with the partial exception of E502T, fail to reach the cell surface and express currents. Although Glu-502 is important for gating (42,43), it clearly plays an additional trafficking role. The possibility that these biophysical and trafficking roles may be separable would rationalize why E502T shows partial surface expression but low currents.…”
Section: Mutantmentioning
confidence: 99%
“…The possibility that these biophysical and trafficking roles may be separable would rationalize why E502T shows partial surface expression but low currents. In addition, the absent or weak currents seen in various Kv1.5 (42) and shaker B⌬ (43) channel mutants at the position equivalent to Glu-502 can now be rationalized as a failure in trafficking rather than purely an effect on channel gating (43).…”
Section: Mutantmentioning
confidence: 99%